2015
DOI: 10.3390/ijms160922781
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Pharmacokinetics of α-Lipoic Acid in Rats

Abstract: α-Lipoic acid (LA) is widely used for nutritional supplements as a racemic mixture, even though the R enantiomer is biologically active. After oral administration of the racemic mixture (R-α-lipoic acid (RLA) and S-α-lipoic acid (SLA) mixed at the ratio of 50:50) to rats, RLA showed higher plasma concentration than SLA, and its area under the plasma concentration-time curve from time zero to the last (AUC) was significantly about 1.26 times higher than that of SLA. However, after intravenous administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…It is not easy to evaluate the pharmacological effects of an antioxidant, but the present study highlighted the efficacy of a chronic discontinuous treatment with lipoic acid once the metabolic disturbances induced by the fructose feeding had been installed in the rats. AL, when absorbed, has a very short half-life (30-40 min after oral and 12 min after intravenous administrations) [66], being rapidly intracellularly uptaken, metabolized, and renally excreted [19,67]. In this context, the benefits of our chronic discontinuous treatment may be partially assigned to dihydrolipoic acid (DHLA), the intracellular active metabolite of AL, which can recycle for a while the AL/DHLA system [17,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…It is not easy to evaluate the pharmacological effects of an antioxidant, but the present study highlighted the efficacy of a chronic discontinuous treatment with lipoic acid once the metabolic disturbances induced by the fructose feeding had been installed in the rats. AL, when absorbed, has a very short half-life (30-40 min after oral and 12 min after intravenous administrations) [66], being rapidly intracellularly uptaken, metabolized, and renally excreted [19,67]. In this context, the benefits of our chronic discontinuous treatment may be partially assigned to dihydrolipoic acid (DHLA), the intracellular active metabolite of AL, which can recycle for a while the AL/DHLA system [17,67,68].…”
Section: Discussionmentioning
confidence: 99%
“…Significant difference in concentration in the basal side was observed only at two time point after 120 min (the low- and middle-concentration groups). However, we considered no enantiolectivity on the LA transport, because the difference was much smaller than that observed in our animal testing [ 15 ]. Permeability rates were linearly correlated ( R 2 > 0.9992) with the initial concentrations of LA at the apical side ( Figure 2 A,B), indicating that transport of LA across Caco-2 cells was not saturated in the concentration range used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported the enantioselective pharmacokinetics of LA in rats [ 15 ]. In that study, we observed that the F h and F a and/or F g of transport from the gastrointestinal tract to the systemic circulation were implicated in these enantioselective pharmacokinetics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5). In the pharmacokinetics studies, it was reported that the maximum plasma concentrations in mice after the oral administration of ALA at 50 and 100 mg/kg were 7.6 ± 1.4 µg/mL (around 36 µM) and 30.9 ± 1.4 µg/mL (around 150 µM), respectively, 38) and that the half-life was around 27 min after the oral administration at 20 mg/kg in rats. 39) Although the actual plasma concentration of ALA in the present study using mice constantly ingesting ALA with the diet was not measured, our results suggested that the mechanisms for the beneficial effects of chronic ALA administration on the clonidine-induced vasodilation could involve the action to aortas.…”
Section: Discussionmentioning
confidence: 99%